A scoping review of evidence of naturally occurring Japanese encephalitis infection in vertebrate animals other than humans, ardeid birds and pigs. - Zoë A Levesque; Michael G Walsh; Cameron E Webb; Ruth N Zadoks; Victoria J Brookes (PLoS Neglected Tropical Diseases)
Japanese encephalitis virus (JEV) is the leading cause of human encephalitis in Asia. JEV is a vector-borne disease, mainly transmitted by Culex mosquitoes, with Ardeidae birds as maintenance hosts and pigs as amplifying hosts. Other vertebrate animal hosts have been suggested to play a role in the epidemiology of JEV. This scoping review followed PRISMA guidelines to identify species in which evidence of naturally occurring JEV infection was detected in vertebrates other than ardeid birds, pigs and people. Following systematic searches, 4372 records were screened, and data were extracted from 62 eligible studies. Direct evidence (virus, viral antigen or viral RNA) of JEV infection was identified in a variety of mammals and birds (not always identified to the species level), including bats, passerine birds (family Turdidae), livestock (cattle [Bos taurus] and a goat [Capra hircus]), carnivores (two meerkats [Suricata suricatta]), and one horse (Equus caballus). Bat families included Pteropodidae, Vespertilionidae, Rhinolophidae, Miniopteridae, Hipposideridae. Indirect evidence (antibodies) was identified in several mammalian and avian orders, as well as reported in two reptile species. However, a major limitation of the evidence of JEV infection identified in this review was diagnostic test accuracy, particularly for serological testing. Studies generally did not report diagnostic sensitivity or specificity which is critical given the potential for cross-reactivity in orthoflavivirus detection. We hypothesise that bats and passerine birds could play an underappreciated role in JEV epidemiology; however, development of diagnostic tests to differentiate JEV from other orthoflaviviruses will be essential for effective surveillance in these, as well as the companion and livestock species that could be used to evaluate JEV control measures in currently endemic regions.